2007
DOI: 10.1111/j.1540-8175.2007.00499.x
|View full text |Cite
|
Sign up to set email alerts
|

Can Transesophageal Pulse‐Wave Tissue Doppler Imaging Be Used to Evaluate Left Ventricular Function?

Abstract: PW tissue Doppler echocardiographic approach during TEE may be suitable for assessment of the left ventricular function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…The routine use of intraoperative TEE has become the standard of practice in many cardiac surgical centers in North America. Although TEE remains important for the assessment of cardiac structure and function during the perioperative setting, recent studies have evaluated its use for the evaluation of systolic and diastolic function using TDI, strain and strain rate imaging . Sevimli et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The routine use of intraoperative TEE has become the standard of practice in many cardiac surgical centers in North America. Although TEE remains important for the assessment of cardiac structure and function during the perioperative setting, recent studies have evaluated its use for the evaluation of systolic and diastolic function using TDI, strain and strain rate imaging . Sevimli et al .…”
Section: Discussionmentioning
confidence: 99%
“…Although TEE remains important for the assessment of cardiac structure and function during the perioperative setting, recent studies have evaluated its use for the evaluation of systolic and diastolic function using TDI, strain and strain rate imaging . Sevimli et al . compared TTE and TEE in 19 nonanesthetized patients using pulse‐wave TDI, demonstrating comparable values for E, A, E/A, S′, and E/E′ with good agreement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion, this study adds to the growing body of evidence indicating that TDI is of clinical relevance in the perioperative setting. Specifically, the tissue Doppler‐derived surrogate of diastolic filling pressure, E/e′, obtained intraoperatively by TEE or perhaps even by a preoperative transthoracic echocardiographic examination, 41,42 may be a useful indicator for predicting early morbid events after cardiac surgery that may even provide information beyond that of baseline LVEF. Importantly, patients with an elevated preoperative E/e′ may need more careful peri‐ and postoperative management than those patients with E/e′ < 8.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that TEE for TDI measurements may be used instead of TTE. 4 Several studies investigated the prognostic significance of intraoperative E/Ea using TEE in patients undergoing cardiac surgery. 5,6 They suggested that E/Ea should be used in peri-and postoperative management of patients undergoing cardiac surgery to predict adverse outcomes.…”
Section: Dear Editormentioning
confidence: 99%